orbitize! v3: Orbit fitting for the High-contrast Imaging Community - Blunt, Sarah; Wang, Jason J; Hirsch, Lea; Tejada, Roberto; Nagpal, Vighnesh; Surti, Tirth Dharmesh; Covarrubias, Sofia; McKenna, Thea; Chávez, Rodrigo Ferrer; Llop-Sayson, Jorge; Arora, Mireya; Chavez, Amanda; et al. (Journal of open source software, 2024)
orbitize! is a package for Bayesian modeling of the orbital parameters of resolved binary objects from time series measurements. It was developed with the needs of the high-contrast imaging community in mind, and has since also become widely used in the binary star community. A generic orbitize! use case involves translating relative astrometric time series, optionally combined with radial velocity or astrometric time series, into a set of derived orbital posteriors. This paper is published alongside the release of orbitize! version 3.0, which has seen significant enhancements in functionality and accessibility since the release of version 1.0 (Blunt et al., 2020).